Non-β-Lactam Allosteric Inhibitors Target Methicillin-Resistant Staphylococcus aureus: An In Silico Drug Discovery Study - Mahmoud A. A. Ibrahim; Khlood A. A. Abdeljawaad; Alaa H. M. Abdelrahman; Othman R. Alzahrani; Fahad M. Alshabrmi; Esraa Khalaf; Mahmoud F. Moustafa; Faris Alrumaihi; Khaled S. Allemailem; Mahmoud E. S. Soliman; Paul W. Paré; Mohamed-Elamir F. Hegazy; et al. (MDPI AG, 2021)
Penicillin-binding proteins (PBPs) catalyze the final stages for peptidoglycan cell-wall bio-synthesis. Mutations in the PBP2a subunit can attenuate β-lactam antibiotic activity, resulting in unimpeded cell-wall formation and methicillin-resistant Staphylococcus aureus (MRSA). A double mutation in PBP2a (i.e., N146K and E150K) is resistant to β-lactam inhibitors; however, (E)-3-(2-(4-cyanostyryl)-4-oxoquinazolin-3(4H)-yl) benzoic acid (QNZ), a heterocyclic antibiotic devoid of a β-lactam ring, interacts non-covalently with PBP2a allosteric site and inhibits PBP enzymatic activity. In the search for novel inhibitors that target this PBP2a allosteric site in acidic medium, an in silico screening was performed. Chemical databases including eMolecules, ChEMBL, and ChEBI were virtually screened for candidate inhibitors with a physicochemical similarity to QNZ. PBP2a binding affinities from the screening were calculated based on molecular docking with co-crystallized ligand QNZ serving as a reference. Molecular minimization calculations were performed for inhibitors with docking scores lower than QNZ (calc. −8.3 kcal/mol) followed by combined MD simulations and MM-GBSA binding energy calculations. Compounds eMol26313223 and eMol26314565 exhibited promising inhibitor activities based on binding affinities (ΔGbinding) that were twice that of QNZ (−38.5, −34.5, and −15.4 kcal/mol, respectively). Structural and energetic analyses over a 50 ns MD simulation revealed high stability for the inhibitors when complexed with the double mutated PBP2a. The pharmacokinetic properties of the two inhibitors were predicted using an in silico ADMET analysis. Calculated binding affinities hold promise for eMol26313223 and eMol26314565 as allosteric inhibitors of PBP2a in acidic medium and establish that further in vitro and in vivo inhibition experimentation is warranted.